Graphene‐Based Nanotechnology in Neurodegenerative Disorders. Issue 3 (1st February 2021) - Tapeinos, Christos
Abstract : Graphene‐based materials (GBMs) demonstrate unique electrochemical, mechanical, thermal, and optical properties rendering them attractive candidates for numerous biomedical applications. Since graphene's discovery, GBMs have been at the forefront of biomedical research offering innovative solutions for numerous diseases, including neurodegenerative disorders (NDs). There are numerous reviews in which synthesis and functionalization methods of GBMs are discussed. However, this review focuses specifically on the recent research advances of GBMs for NDs, and more specifically, on sensing and therapeutic applications. After a short description of NDs' main characteristics, significant attention is given to the functionalization strategies used to improve the biomedical properties of GBMs, and recent applications for Alzheimer's disease, Parkinson's disease, Huntington's disease, multiple sclerosis, and amyotrophic lateral sclerosis. A description of the use of GBMs and neural stem cell technology and known toxicity issues, followed by several limitations that current GBMs need to overcome, completes this review. Abstract : Graphene‐based materials (GBMs) constitute a class of materials with unique electrochemical, mechanical, thermal, and optical properties. These properties render them attractive candidates for the treatment of neurodegenerative diseases either as therapeutic or diagnostic applications. Herein, functionalization strategies, toxicity, stem cell technology, and several references to biosensing, bioimaging, bioelectronics, and drug/gene delivery are presented.